(untitled) (Proceedings of International Educators Conference, 2024)
Nosebleeds (epistaxis) - bleeding from the nasal cavity, usually it can be seen as bleeding from the nose. There are two types of nosebleeds: anterior (the most common) and posterior (less common, but requiring more attention from a doctor). Sometimes, in more severe cases, blood can rise from the nasolacrimal canal and exit the eye socket. Fresh and coagulated blood can enter the stomach and cause nausea and vomiting. Nosebleeds rarely end in death; for example, in the USA during 1999, among 2.4 million deaths, only 4 cases of death from epistaxis were recorded.